Managing Outdoor Recreation Case Studies in the National Parks - Manning, Robert E.; Anderson, Laura E.; Pettengill, Peter (CAB International, 2017)
This fully updated second edition presents a conceptual framework of outdoor recreation management in the form of a series of management matrices. It then illustrates this framework through new and updated case studies in US national parks and concludes with the principles of outdoor recreation management. Written by a team of authors with extensive academic and practical experience in the field of outdoor recreation, the book: develops and presents a matrix-based framework of strategies and practices for managing outdoor recreation in a sustainable way; illustrates applications of the best management practices through a series of case studies in diverse national parks; includes lecture slides and online matrices to aid the teaching of outdoor recreation management to a new generation.